Depiction Of Moral Values In Indonesian English Junior High School Textbooks - Imansari, Fillah Pertiwi (JUPE : Jurnal Pendidikan Mandala, 2024)
Most language textbooks are analyzed by emphasizing cultural/multicultural content, gender stereotypes/representation, neoliberalism, and pedagogical representation. The role of language textbooks on moral and cultural values at various levels has been examined.  However, moral values at the junior high school level are scarce. This study examined the moral values in junior high school English textbooks entitled “English for Nusantara” for grades 7 and 8 published by the Indonesian Education Standard, Curriculum, and Assessment Agency of the Ministry of Education Culture, Research and Higher Education within the independent curriculum. This research used a qualitative content analysis research design. This study adopted the Moral Foundations Theory Framework (MTF) Graham presented a set of moral principles such as care/harm, fairness/cheating, loyalty/betrayal, authority/subversion, and sanctity/degradation. The result showed that both the textbooks for grades 7 and 8 were similar representing more dominant moral values than bad values, with percentages of 95% and 59%, respectively. The other finding suggested that the textbooks did not integrate authority, loyalty, and fairness. The study implies incorporating stories that highlight moral values should be required to internalize ethical values and encourage students to do good things.